A clinical dilemma, the diagnosis of ectopic pregnancy - Carlos Moya Toneut; Javier Cruz Rodríguez; Miguel Román Sarduy Nápoles (Acta Médica del Centro)
Introduction: ectopic pregnancy is currently a world of health problem. The increase in its incidence is attributed to the difficulties in the diagnosis that are often presented and to the morbidity and mortality that derive from it. It is one of the first causes of death in the first quarter of pregnancy. Objective: assess ectopic pregnancy as a clinical dilemma for diagnosis. Methods: a narrative bibliographic review was carried out that included various texts, articles, printed and digital materials related to ectopic pregnancy. The databases and directories Scielo, Lilacs, Latindex, Medline and Scopus were consulted, through the keywords in Spanish and Bollean operators to expand the results: “Hemorrhages” and “Ectopic pregnancy”. 22 original and review articles were selected, in the national and international context, published between 2000 and 2020. Development: in every nosological illness a good interrogation and a physical examination favor the diagnosis, however difficult it may be. Following the steps of the clinical method helps to obtain an appropriate and timely diagnosis. It is transcendental that the doctor knows the pathophysiology and the clinical elements in ectopic pregnancy, which can go to look in an exquisite interrogation and a detailed physical examination. Conclusions: the diversity of possible clinical presentations has led to "the great simulator of gynecology", so it constitutes a clinical dilemma its diagnosis in the different levels of health care.